Mannoprotein MP84 mediates the adhesion of Cryptococcus neoformans to epithelial lung cells - Teixeira, Pedro A. C.; Penha, Luciana L.; Mendonça-Previato, Lucia; Previato, Jose O. (Frontiers in Cellular and Infection Microbiology, 2014)
The capsule is the most important virulence factor of the fungal pathogen Cryptococcus neoformans. This structure consists of highly hydrated polysaccharides, including glucuronoxylomannan (GXM), and galactoxylomannan (GalXM). It is also composed of mannoproteins (MPs) which corresponds to less than 1% of the capsular weight. Despite MPs being the minority and least studied components, four of these molecules with molecular masses of 115, 98, 88, and 84 kDa were identified and characterized as C. neoformans immunoreactive antigens involved in the pathogenesis, and are potential cryptococcosis vaccine candidates. With the aim to describe the adhesive property of MPs, we cloned and expressed the MP84, a mannoprotein with molecular weight of 84 kDa, on Pichia pastoris yeast, and performed interaction assays of C. neoformans with epithelial lung cells, in the presence or absence of capsule components. Two fungal strains, the wild type, NE-241, and a mutant, CAP67, deficient in GXM production, were used throughout this study. The adhesion assays were completed using epithelial lung cells, A549, and human prostate cancer cells, PC3, as a control. We observed that capsulated wild type (NE-241), and acapsular (CAP67) strains adhered significantly to A549 cells, compared with PC3 cells (p < 0.05). GXM inhibits the NE-241 adhesion, but not the CAP67. In contrast, CAP67 adhesion was only inhibited in the presence of MP84. These results demonstrate the involvement of MP in the adhesion of C. neoformans to epithelial lung cells. We conclude that this interaction possibly involves an adhesion-like interaction between MP on the fungal surface and the complementary receptor molecules on the epithelial cells.